h - Bernstein, Daniel J.; Lange, Tanja; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the Third International Conference on Cryptology in Africa, AFRICACRYPT 2010, held in Stellenbosch, South Africa, on May 3-6, 2010. The 25 papers presented together with three invited talks were carefully reviewed and selected from 82 submissions. The topics covered are signatures, attacks, protocols, networks, elliptic curves, side-channel attacks and fault attacks, public-key encryption, keys and PUFs, and ciphers and hash functions.
Signatures -- A New RSA-Based Signature Scheme -- Fair Blind Signatures without Random Oracles -- Fair Partially Blind Signatures -- Attacks -- Parallel Shortest Lattice Vector Enumeration on Graphics Cards -- Flexible Partial Enlargement to Accelerate Gröbner Basis Computation over -- Factoring RSA Modulus Using Prime Reconstruction from Random Known Bits -- Protocols -- Proofs of Restricted Shuffles -- Batch Range Proof for Practical Small Ranges -- Optimistic Fair Priced Oblivious Transfer -- Networks -- Information-Theoretically Secure Key-Insulated Multireceiver Authentication Codes -- Simple and Communication Complexity Efficient Almost Secure and Perfectly Secure Message Transmission Schemes -- Communication Efficient Perfectly Secure VSS and MPC in Asynchronous Networks with Optimal Resilience -- Elliptic Curves -- Avoiding Full Extension Field Arithmetic in Pairing Computations -- ECC2K-130 on Cell CPUs -- Side-Channel Attacks and Fault Attacks -- Practical Improvements of Profiled Side-Channel Attacks on a Hardware Crypto-Accelerator -- Differential Fault Analysis of HC-128 -- Fresh Re-keying: Security against Side-Channel and Fault Attacks for Low-Cost Devices -- Public-Key Encryption -- Strong Cryptography from Weak Secrets -- Efficient Unidirectional Proxy Re-Encryption -- Public-Key Encryption with Non-Interactive Opening: New Constructions and Stronger Definitions -- Keys and PUFs -- Flexible Group Key Exchange with On-demand Computation of Subgroup Keys -- Quantum Readout of Physical Unclonable Functions -- Ciphers and Hash Functions -- Parallelizing the Camellia and SMS4 Block Ciphers -- Improved Linear Differential Attacks on CubeHash -- Cryptanalysis of the 10-Round Hash and Full Compression Function of SHAvite-3-512.
Keywords: Computer science; Computer Communication Networks; Operating systems (Computers).; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Systems and Data Security; Operating Systems